2020
DOI: 10.1038/s41598-020-70741-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use and hygiene interact to influence the distribution of antimicrobial-resistant bacteria in low-income communities in Guatemala

Abstract: To examine the effects of poor sanitation and hygiene on the prevalence of antimicrobial-resistant bacteria, we surveyed households in two rural and two urban communities in Guatemala (N = 196 randomly selected households). One adult (≥ 18-years old) and, when available, one child (≤ 5 yearsold) provided a stool sample. Up to 48 presumptive Escherichia coli isolates were collected from each stool sample (n = 21,256 total) and were subjected to breakpoint assays for ten antibiotics. Mixedeffects logistic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Low hygiene levels, lack of clean water, or poor sanitary conditions can create perfect conditions for the development and transmission of infections [ 66 ]. In addition to that, Farhani et al [ 67 ] have total of 80 E. coli isolates, separated into 51 different genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Low hygiene levels, lack of clean water, or poor sanitary conditions can create perfect conditions for the development and transmission of infections [ 66 ]. In addition to that, Farhani et al [ 67 ] have total of 80 E. coli isolates, separated into 51 different genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypically, we compared breakpoint assay results with wholegenome sequence data for > 730 E. coli isolates and found that for the most common antibioticresistance phenotypes (ampicillin, streptomycin, sulfamethoxazole, tetracycline and trimethoprim), diagnostic sensitivity varied between 0.75 0.93 while diagnostic speci city ranged from 0.94 and 0.99 [34]. Phenotypically, we found a correlation (r) of 0.98 between a panel of E. coli isolates by breakpoint and Kirby Bauer disc diffusion test [37]. Lastly, there was some mismatch between the antibiotics tested in this study and those used by the study community.…”
Section: Discussionmentioning
confidence: 90%
“…Lastly, there was some mismatch between the antibiotics tested in this study and those used by the study community. We used identical methods in a different study, which included both antibiotics, and found a correlation of 0.73 between the two resistance phenotypes [37]. Antibiotics that were not included in the assays were those that were either redundant to the panel of antibiotics being used, (e.g., tetracycline vs. doxycycline, ceftazidime vs. other cephalosporins) or were not expected to affect E. coli (e.g., metronidazole).…”
Section: Discussionmentioning
confidence: 99%
“…Colony morphology, while not a reliable diagnostic for species identity, was 99.2% consistent with E. coli based on a random subset of 248 isolates. We have successfully used this method for selecting E. coli for high-throughput assessment of antibiotic resistance in other studies [16,[36][37][38]. Thirdly, the "breakpoint" assay, which is not considered a diagnostic tool in a clinical microbiology lab, provides a low-cost means to analyze many isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the "breakpoint" assay, which is not considered a diagnostic tool in a clinical microbiology lab, provides a low-cost means to analyze many isolates. We have assessed the validity of this method genotypically [36] and phenotypically [38].…”
Section: Discussionmentioning
confidence: 99%